Organogenesis and Ultrastructural Features ofIn VitroGrownCanna indicaL. - Wafa, Sharifah Nurashikin; Taha, Rosna Mat; Mohajer, Sadegh; Mahmad, Noraini; Ahmed, Bakrudeen Ali (Hindawi Publishing Corporation, 2016)
An efficient protocol for micropropagation of Canna indica L., an economically and pharmaceutically important plant, was standardized using rhizome explants, excised from two-month-old aseptic seedlings. Complete plant regeneration was induced on MS medium supplemented with 3.0 mg/L BAP plus 1.5 mg/L NAA, which produced the highest number of shoots (73.3 ± 0.5%) and roots (86.7 ± 0.4%) after 2 weeks. Furthermore, the optimum media for multiple shoots regeneration were recorded on MS enriched with 7.0 mg/L BAP (33.0 ± 0.5%). Plantlets obtained were transplanted to pots after two months and acclimatized in the greenhouse, with 75% survival. In addition, ultrastructural studies showed that rhizomes of in vitro grown specimens were underdeveloped compared to the in vivo specimens, possibly due to the presence of wide spaces. Meanwhile, the leaves of in vivo specimens had more open stomata compared to in vitro specimens, yet their paracytic stomata structures were similar. Hence, there were no abnormalities or major differences between in vitro regenerants and mother plants.